Determinants of practice location choices among physicians and medical students in Mali: Insights into addressing medical deserts through evidence-based strategies. - Issa Kalossi; Dielika Coulibaly; Kassoum Alou N'Diaye; Modibo Salia Drame; Djibril Sissoko; Thiery Almont; Kassoum Kayentao (PLOS Global Public Health)
The shortage of medical professionals in rural and remote areas is a global issue that significantly challenges equitable healthcare delivery. Worldwide, various studies have examined the motivations of medical professionals in choosing their practice location. However, for Mali, this topic remains underexplored, motivating us to conduct this study to identify factors influencing physicians' workplace decisions in Mali. We conducted a cross-sectional study targeting physicians and final-year medical students. Using simple random sampling, we selected 358 respondents, 69% of whom were physicians. Data were collected via structured questionnaires assessing sociodemographic characteristics, professional aspirations, and factors influencing workplace preferences. Multivariate logistic regression was used to identify factors independently associated with rural practice preference. Approximately 38% of the respondents preferred rural areas for their practice, primarily citing career development and opportunities for continuing education (38%). The likelihood of choosing rural practice was higher (OR = 5.09; 95% CI = 2.52-10.8) among participants with family residing in rural areas. This study highlights both personal and systemic factors shaping physicians' workplace choices in Mali. Interventions aimed at strengthening rural practice appeal should prioritize professional development opportunities and support systems for those with rural backgrounds. Tailored strategies addressing these motivations could enhance equitable healthcare workforce distribution in Mali.